Calibration of analyzers of the mobile communication system parameters - Meshcheriak, Oleh; Velychko, Oleh (Видавництво Львівської політехніки, 2022)
The creation and operation of mobile communication systems is impossible without determining the parameters of base stations and mobile communication systems. For these purposes, appropriate devices are used that optimally combine testing capabilities in a single portable solution, which eliminates the need for several separate control and measuring devices. One of the main types of measurements of such devices is the measurement of the power of ultra-high and extremely high frequency signals. The article presents the method of calibrating meters of directional and absorbed power of ultra-high and extremely high frequency signals using the Bird 5000-EX mobile communication system parameter analyzers complete with the Power Sensor 5010V sensor and measuring sensors, Anritsu CellMaster MT8212EA and Arnitsu SiteMaster S331E spectrum analyzers. Calibration schemes for analyzers of parameters of mobile communication systems and analyzers of mobile communication base stations (hereinafter referred to as analyzers) have been developed. A measurement model of the analyzers based on the parameters of the directional and absorbed power of ultra-high and extremely high frequency signals based on the developed calibration schemes was created. The contribution of each component of the measurement model to the calibration result and the corresponding uncertainties of the model components were determined. The measurement uncertainty budget was made based on the proposed analyzer calibration model. The influence of the most significant influential values on the accuracy of measurement results was analyzed. The content of quantitative and qualitative indicators of corrections, which must be taken into account during calibration to achieve the highest accuracy of measurements, is revealed. The practical results of studies of measurement instability are given. The analyzer calibration method described in the article can be used in calibration laboratories that have the appropriate equipment and standards.
Keywords: Directional power; Absorbed power; Parameter analyzer; Calibration; Measurement uncertainty